False Low Beta-hCG in a Complete Hydatidiform Molar Pregnancy: A Case of Hook Effect - Sah, Sanjay Kumar; Shah, Pravin; Sherpa, Ang Dali (Med Phoenix, 2024)
Introduction: Hydatidiform molar pregnancy presents as a proliferative disorder of trophoblastic cells. Complete hydatidiform molar pregnancy presents typically with abnormally high levels of beta human chorionic gonadotropin (β-hCG). The high level of β-hCG is taken as a marker in its diagnosis and follows up. However, many a times very high levels of β-hCG may be associated with falsely low or negative β-hCG levels because of “Hook effect”. The hook effect occurs with extremely high levels of β-hCG, saturating detection antibodies, leading to falsely low laboratory results. If unrecognized, this can lead to misdiagnosis and a delayed therapy or mismanagement of care that may have a negative treatment outcome. Here, we report a case of Hook effect presented to Emergency Department of a tertiary care center, National Medical College Teaching Hospital, Birgunj, Nepal.